Memprediksi Minat Karier dan Pilihan Aspirasi Terhadap Pertimbangan Pilihan Karier Berdasarkan Social Cognitive Career Theory (SCCT) - Sa’idah, Ishlakhatus (JKI (Jurnal Konseling Indonesia), 2018)
This research aims to predict the model interest Social Cognitive career Theory (SCCT) through a test run to 600 high school students in Gresik Regency. Subject completed measures of self-efficacy in career, expectations of a result, interests, support and social barriers, and considerations in the choice of six types of RIASEC Holland (1997). Model options integrated interest meets the data well in all types of Holland and generally supports the hypothesis that self-efficacy and outcome expectations are similarly predict the interest, and that interest in self-efficacy mediate the relationships and expectations the results for the consideration of the options. Contrary to SCCT, support and social barriers related considerations the option indirectly i.e. via self-efficacy. The implications of these findings for further research is the importance of cross-cultural validity of consideration on the SCCT<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">